Investigation of random lasing from all-inorganic halide perovskite quantum dots prepared under ambient conditions. Issue 5 (3rd February 2021) - Zhang, Deng-Gui; Jian, Liang-Yu; Tseng, Zong-Liang; Cheng, Hsin-Ming; Lin, Ja-Hon
Abstract : Random lasing from CsPbBr3 quantum dots (QDs) prepared by the hot injection method under ambient conditions has been demonstrated. The random laser produced a speckle reduced image with a contrast of around 0.051. Abstract : Random lasing from CsPbBr3 quantum dots (QDs) prepared by the hot injection method under ambient conditions has been investigated. The lasing characteristics and performance were related to the thickness and aggregation of the QDs film on a glass substrate. The perovskite emitted linear polarized ASE from the edge of the prepared sample as pump energy above a certain threshold, owing to the gain guiding effect. In comparison to the Q-switched Nd:YAG laser, the prepared perovskite random lasers produced a speckle reduced image with a lower contrast of around 0.051. Through temperature-dependent measurements under a surface normal emission configuration, the photon energy of ASE revealed a red shift as the temperature increased and showed a larger characteristic temperature of around 230 K. This result illustrates that the perovskite prepared under ambient conditions can be a promising material for a microcavity laser in the near future.